Targeting of colorectal cancer organoids with zoledronic acid conjugated to the anti-EGFR antibody cetuximab - Roberto Benelli; Alessandro Poggi; Delfina Costa; Laura Salvini; Samuele Tardito; Francesca Tosetti; Federico Villa; Maria Raffaella Zocchi (Journal for ImmunoTherapy of Cancer, 2022)
Background Antibody-drug conjugates (ADC) are essential therapeutic options to treat solid and hematological cancers. The anti-epidermal growth factor-receptor (EGFR) antibody cetuximab (Cet) is used for the therapy of colorectal carcinoma (CRC). Anti-CRC Vδ2 cytolytic T lymphocytes can be elicited by the priming of tumor cells with the aminobisphosphonate zoledronic acid (ZA) and consequent presentation of isopentenyl pyrophosphates through butyrophilin (BTN) family members such as BTN3A1 and BTN2A1. A major drawback that impairs the targeting of ZA to CRC is the bone tropism of aminobisphosphonates.Methods The phosphoric group of ZA was linked to free amino groups of Cet in the presence of imidazole following the labeling of phosphoric groups of DNA to amino groups of proteins. The generation of Cet-ZA ADC was confirmed by matrix assisted laser desorption ionization mass spectrometry and inductively coupled plasma-mass spectrometry analysis. Thirteen CRC organoids were obtained with a chemically defined serum-free medium in Geltrex domes. Proliferation and activation of cytolytic activity against CRC organoids by Vδ2 T cells was detected with flow cytometry, crystal violet and cytotoxic probe assays and image analysis. Immunohistochemistry and quantification of BTN3A1 or BTN2A1 expression and the number of tumor infiltrating Vδ2 T cells in CRC were performed by automatic immunostaining, whole slide scanning and computerized analysis of digital pathology imaging.Results The novel ADC Cet-ZA was generated with a drug antibody ratio of 4.3 and displayed a reactivity similar to the unconjugated antibody. More importantly, patient-derived CRC organoids, or CRC tumor cell suspensions, could trigger the expansion of Vδ2 T cells from peripheral blood and tumor infiltrating lymphocytes when primed with Cet-ZA. Furthermore, Cet-ZA triggered Vδ2 T cell-mediated killing of CRC organoids. The expression of BTN3A1 and BTN2A1 was detected not only in CRC organoids but also in CRC specimens, together with a considerable amount of tumor infiltrating Vδ2 T cells.Conclusions These findings are proof of concept that the Cet-ZA ADC can be used to target specifically CRC organoids and may suggest a new experimental approach to deliver aminobisphosphonates to EGFR+ solid tumors.